New York's burned-over district : a documentary history - McBride, Spencer W.; Dorsey, Jennifer Hull, 1969- (Cornell University Press, 2023)
"New York's Burned-over District uses primary source documents to tell the story of how Christian revivalism transformed central and western New York into a critical hub of social reform in nineteenth-century America"--